A Rare Case of Ovarian Double-Hit/Diffuse Large B-Cell Lymphoma: A Case Report and Review of Literature - Madhulika Urella MD; Kemnasom Nwanwene MD; Adarsh Sidda MD; Toni Pacioles MD (SAGE Publishing, 2023)
Primary ovarian non-Hodgkin lymphoma is a rare lymphoma that is often associated with diagnostic delays, initial misdiagnosis, and inappropriate management. We report a case of ovarian diffuse large B-cell lymphoma (DLBCL) in a young female who initially presented with generalized fatigue, lower abdominal discomfort, and 40 pounds of unintentional weight loss. She subsequently had a computed tomography of abdomen done that showed fatty liver, hepatomegaly, and a left heterogeneous ovarian mass measuring about 4 × 4.2 cm. Transvaginal ultrasound was also done that showed a heterogeneous solid left adnexal mass measuring 7.4 × 5.6 × 6.6 cm. She subsequently had a total abdominal hysterectomy with bilateral salpingo-oophorectomy. Immunohistochemistry (IHC) showed the malignant cells expressing PAX5, CD20, and BCL2 with a Ki-67 proliferation index greater than 90%. The cells were negative for AE1/AE3, S100, CD30, and cyclin D1. Aggressive B-cell lymphoma fluorescence in situ hybridisation (FISH) panel was positive for rearrangement of BCL6 and MYC, with no evidence of BCL2 rearrangement, consistent with a double-hit high-grade B-cell lymphoma. Immunohistochemistry for BCL6 and MU M1 showed positive staining in the malignant cells. CD10 was negative. The staining profile was consistent with nongerminal center B-cell-like type of DLBCL. Ovarian lymphoma is a very rare entity; the presence of an enlarged ovarian tumor should raise the suspicion of ovarian lymphoma, and our case also emphasizes on the use of IHC markers in diagnosing the ovarian DLBCL.